Cyclic Fractional Plastic Model for Granular Soils - Li, Ye; Sun, Yifei; Ju, Wen (Frontiers in Built Environment, 2019)
Granular soils, e.g., sand, ballast, and rockfill, usually experience dynamic loads in the field. Traditional constitutive models for monotonic loading conditions cannot be used for advanced characterization of the complex loading behavior of granular soils. In this study, a simple fractional plastic model is developed, based on the generalized fractional plastic flow rule which considers the loading and unloading differences under triaxial compression and extension conditions. The model is further validated against a series of cyclic loading behavior of different granular soils, where a good predicting performance is observed.